Information system for the Third World - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The UNDP has established an information system designed to improve information exchange and cooperation between Third World countries. Its INRES system contains information in French, Spanish and English on more than 2,600 institutions that offer...